PELATIHAN PEMBUATAN KERAJINAN TANGAN DARI BENANG MACRAME YANG BERNILAI EKONOMIS PADA SISWA SDIT INSANTAMA KENDARI - La Tarifu; Rizal Rizal; Sartono Sartono; Jopang Jopang; Bakti Bakti; Rahmah Djauziyah Patola; Ratna Sari Dewi; Rizka Ananda Chaisarah; Veni Restu Yolita (Universitas Halu Oleo, 2023)
This training was carried out for community empowerment in the preparation of Community Service Plans (PKM) for SDIT Insantama Kendari Students in Mokoau Village, Kambu District, Kendari City, Southeast Sulawesi in the form of diversification of handicraft products from macramé threads so as to create community welfare through optimizing the potential of macramé threads from semi-finished goods to finished goods. The method used in this activity is the provision of material, direct practice and mentoring. The material was given in the SDIT Insantama Kendari hall, with material on the creative economy and direct training to introduce various alternative options for creativity and young entrepreneurship with materials that are easy to find in the surrounding environment to SDIT Insantama Kendari students with assistance from SDIT Insantama Kendari teachers. Techniques for making handicrafts from macramé threads with assistance and the practice of making crafts from macramé threads. The results of this activity show that (1) trainees can make handicrafts from macramé threads with the right techniques, (2) trainees can make this training activity the beginning of young entrepreneurship (3) videos of making handicrafts from macramé threads published on YouTube